An Investigation into Omani Physical Education Teachers' Beliefs about Physical Education Teachers' Characteristics and their Roles in Omani Schools - Nasser Yasser Al-Rawahi (Sultan Qaboos University, 2010)
The purpose of this study was to investigate Omani physical education teachers‟ (pre -service and in-service) beliefs about the characteristics and roles of physical education teachers in Omani schools. Interviews were used to achieve this purpose by interviewing 29 participants: 12 student teachers and 17 teachers. Data were analysed qualitatively by using analytic induction and interpretive analytic framework. Qualitative results show that student teachers and teachers have similar beliefs about the general and professional characteristics of a physical education teacher. Between 70% and 95% of participants believed that the essential general characteristics of physical education teachers are: having a strong personality, being an ideal model for students, having patience and tolerance, and communicating effectively with students. Also, similar beliefs were found among the participants regarding the professional characteristics. They believed that a successful physical education teacher is one who has conviction about his profession, and who is always physically fit in order to be able to manage all of the profession‟s requirements in or out of school. Results also indicated that student teachers believed in traditional roles of the teacher who is more concerned about giving knowledge to students, while experienced teachers believe in progressiv teaching roles of the teacher who facilitates students‟ learning. All the results are discussed in relation to the physical education context in Oman.